2019
DOI: 10.3389/fpls.2019.00118
|View full text |Cite
|
Sign up to set email alerts
|

Cytological, Biochemical and Molecular Events of the Embryogenic State in Douglas-fir (Pseudotsuga menziesii [Mirb.])

Abstract: Somatic embryogenesis techniques have been developed for most coniferous species, but only using very juvenile material. To extend the techniques’ scope, better integrated understanding of the key biological, physiological and molecular characteristics of embryogenic state is required. Therefore, embryonal masses (EMs) and non-embryogenic calli (NECs) have been compared during proliferation at multiple levels. EMs and NECs originating from a single somatic embryo (isogenic lines) of each of three unrelated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 106 publications
(161 reference statements)
4
32
0
Order By: Relevance
“…To date, many authors have distinguished EC from NEC based on morphological and histological studies [51,52,53]. Biochemical comparison of these tissues showed that carbohydrates, phytohormones and free amino acids differentially accumulated in EC and NEC [32,54,55]. When comparing metabolomic and hormonal profiles of EC and NEC, we were able to identify metabolic markers of the embryogenic state that can be directly used to pilot the optimization of the composition of the culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, many authors have distinguished EC from NEC based on morphological and histological studies [51,52,53]. Biochemical comparison of these tissues showed that carbohydrates, phytohormones and free amino acids differentially accumulated in EC and NEC [32,54,55]. When comparing metabolomic and hormonal profiles of EC and NEC, we were able to identify metabolic markers of the embryogenic state that can be directly used to pilot the optimization of the composition of the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolite profiles in our study showed that NEC accumulated starch reserves, while EC highly accumulated maltotriose, a product of starch hydrolysis. Gautier et al [32] also observed large structures of starch reserves in NEC of Douglas-fir ( P. menziesii ) and hypothesized that NEC main fate was survival while EC was a transient state before fate transition. We highlight here for the first time that maltotriose is the preferred way to store sugars in EC for a faster usage during fate transition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forests composed of superior genotypes will yield genetic gains much faster than those that could occur by natural selection (Pullman et al., 2003 ). However, the molecular regulatory mechanisms that induce SE in conifers remain unknown (Gautier et al., 2019 ; Pullman et al., 2015 ). Many conifer genotypes are recalcitrant to SE induction (Pullman et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%